Moderate maize canopy defoliation improves light distribution, crop yields, and soybean seed quality in additive maize-soybean intercropping - Muhammad Ali Raza; Wang Zhiqi; Amjad Saeed; Hina Gul; Hassan Shehryar Yasin; Asif Naveed Ranjha; Zaheer Ahmed; Ghulam Raza; Wopke Van Der Werf; Akash Fatima; Xue Liang; Muhammad Hayder Bin Khalid; et al. (Field Crops Research, 2026)

Nanoparticles of thiolated gum ghatti for the controlled ocular delivery of Ciprofloxacin - Muhammad Abu Sufian; Shahid Shah; Akhtar Rasul; Nabeel Ahmad; Ghulam Abbas; Muhammad Hanif; Saleha Babar; Azka Fatima; Omeira Iqbal; Maira Tahir; Nader I. Namazi (DARU Journal of Pharmaceutical Sciences, 2026)

Modeling the impact of climate warming on tomato phenology - Shakeel Ahmad; Ghulam Abbas; Zartash Fatima; Sajjad Hussain; Muhammad Ali Khan; Mukhtar Ahmed; Carol Jo Wilkerson; Gerrit Hoogenboom (Agricultural and Forest Meteorology, 2025)

Recent advances in beta-type hexagonal ferrites: Synthesis, structural, vibrational and electromagnetic characteristics - M. Irfan; Shafaq Waqar; Hafiz Ghulam Shabbir; Tehreem Idrees; Fatima Khan; Komel Maryam; Maryam Choudhary; Isbah Shamshad; Abdul Rehman Ashiq; Shagufta Gulbadan; Muhammad Azhar Khan; Nayyab Sajjad (Next Research, 2025)

Assessment of Climate Change Impact on Potato-Potato Cropping System Under Semi-arid Environment and Designing of Adaptation Strategies - Sahrish Naz; Mukhtar Ahmed; Ghulam Abbas; Zartash Fatima; Sajjad Hussain; Pakeeza Iqbal; Abdul Ghani; Muhammad Ali; Tahir Hussain Awan; Noreen Samad; Muhammad Aasim; Sezai Ercisli; et al. (Potato Research, 2025)

Role of Melatonin in Leaf Gas Exchange by Redox Regulation, K+ Homeostasis and Gene Expression in Canola Under Salinity Stress - Muhammad Ali; Muhammad Farooq; Adnan Noor Shah; Ghulam Hassan Abbasi; Salman Ahmad; Aasma Parveen; Birhanu Iticha; Muhammad Riaz; Muhammad Kamran; Fatima Nisar (Journal of Soil Science and Plant Nutrition, 2025)

Morphometric and molecular characterization of Channa marulius from Riverine system of Punjab, Pakistan - Ghulam Rabbani; Fayyaz Rasool; Mahroze Fatima; Muhammad Bilal Bin Majeed (Molecular Biology Reports, 2024)

Biochar and PGPR: A Winning Combination for Peanut Growth and Nodulation under Dry Spell - Tashfeen Alam; Fatima Bibi; Hunaiza Fatima; Faiza Munir; Alvina Gul; Ghulam Haider; Muhammad Jahanzaib; Rabia Amir (Journal of Soil Science and Plant Nutrition, 2024)

Evaluation of carob tree (Ceratonia siliqua L.) pods, through three different drying techniques, and ultrasonic assisted extraction, for presence of bioactives - Ashiq Hussain; Muhammad Rehan Arif; Adnan Ahmed; Salah Laaraj; Nida Firdous; Muhammad Qasim Ali; Haya Fatima; Shazia Yaqub; Samina Kauser; Rizwan Nisar; Faiza Iftikhar Gorsi; Ghulam Mueen Ud Din; et al. (South African Journal of Botany, 2024)

Genetic Association Among Morpho-Physiological Attributes Against Heat Tolerance in Rice Genotypes - Hafiz Ghulam Muhu-Din Ahmed; Noor Fatima; Yawen Zeng; Muddassir Hussain; Muhammad Moaaz Mushtaq; Ghulam Sabir Hussain; Muhammad Irfan Akram; Amjad Saeed; Adnan Noor Shah; Hayssam M. Ali; Mohamed M. A. Abdelhamid; Sezai Ercisli (Journal of Crop Health, 2024)

Trapping the genetic variation for yield and yield related attributes in bread wheat under water deficit stress - Hafiz Ghulam Muhu-Din Ahmed; Muhammad Naeem; Yawen Zeng; Aziz Ullah; Ghulam Sabir Hussain; Muhammad Irfan Akram; Amjad Saeed; Noor Fatima; Ibtasam Moeez; Hayssam M. Ali; Nagy S. Radwan; Sezai Ercisli; et al. (Euphytica, 2024)

Heritability and Genotypic Association Among Seedling Attribute Against Salinity Stress Tolerance in Wheat Genotypes for Sustainable Food Security - Hafiz Ghulam Muhu-Din Ahmed; Yawen Zeng; Xiaomeng Yang; Anns Faisal; Noor Fatima; Aziz Ullah; Ghulam Sabir Hussain; Muhammad Iftikhar; Muhammad Rizwan Anwar (Journal of Crop Health, 2024)

Plant Growth-Promoting Rhizobacteria Significantly Improves Growth Attributes and Photosynthetic Machinery in Wheat - Tahir Naqqash; Mahreen Fatima; Saif-ur-Rehman; Sherien Bukhat; Muhammad Shahid; Ghulam Shabir; Muhammad Tahir; Muhammad Arshad; Muhammad Babar (Journal of Plant Growth Regulation, 2022)

Application of CSM-CANEGRO Model for Climate Change Impact Assessment and Adaptation for Sugarcane in Semi-arid Environment of Southern Punjab, Pakistan - Muhammad Nadeem; Muhammad Nazer Khan; Ghulam Abbas; Zartash Fatima; Pakeeza Iqbal; Mukhtar Ahmed; Muhammad Ali Raza; Abdul Rehman; Ehsan Ul Haq; Akbar Hayat; Muhammad Ali; Shakeel Ahmad (International Journal of Plant Production, 2022)

Uncovering the role of melatonin in plant stress tolerance - Ahsan Ayyaz; Aneela Kanwal Shahzadi; Saba Fatima; Ghulam Yasin; Zafar Ullah Zafar; Habib-ur-Rehman Athar; Muhammad Ahsan Farooq (Theoretical and Experimental Plant Physiology, 2022)

Modelling Climate Uncertainty and Adaptations for Soybean-Based Cropping System - Maryam Ejaz; Ghulam Abbas; Zartash Fatima; Pakeeza Iqbal; Muhammad Ali Raza; Ahmed M. S. Kheir; Mukhtar Ahmed; Khair Muhammad Kakar; Shakeel Ahmad (International Journal of Plant Production, 2022)

Appraising growth, daily intake, health risk index, and pollution load of Zn in wheat (Triticum aestivum L.) grown in soil differentially spiked with zinc - Abid Ejaz; Zafar Iqbal Khan; Kafeel Ahmad; Fatima Ghulam Muhammad; Shahzad Akhtar; Muhammad Iftikhar Hussain (Environmental Science and Pollution Research, 2022)

Effects of diverse irrigation with wastewater in soil and plants: assessing the risk of metal to the animal food chain - Zafar Iqbal Khan; Fatima Ghulam Muhammad; Kafeel Ahmad; Shahzad Akhtar; Muhammad Sohail; Muhammad Nadeem; Shahzadi Mahpara; Muhammad Umer Farooq Awan; Mona S. Alwahibi; Mohamed S. Elshikh; Muhammad Iftikhar Hussain (Environmental Science and Pollution Research, 2022)

Ecological risk assessment of heavy metal chromium in a contaminated pastureland area in the Central Punjab, Pakistan: soils vs plants vs ruminants - Fu Chen; Fatima Ghulam Muhammad; Zafar Iqbal Khan; Kafeel Ahmad; Muhammad Nadeem; Shahid Mahmood; Muhammad Umar Farooq Awan; Mudasra Munir; Ifra Saleem Malik; Asma Ashfaq; Razia Sultana; Ayesha Maqsood; et al. (Environmental Science and Pollution Research, 2022)

Evaluation of potential ecological risk and prediction of zinc accumulation and its transfer in soil plants and ruminants: public health implications - Fu Chen; Laraib Saqlain; Jing Ma; Zafar Iqbal Khan; Kafeel Ahmad; Asma Ashfaq; Razia Sultana; Fatima Ghulam Muhammad; Ayesha Maqsood; Majida Naeem; Ifra Saleem Malik; Mudasra Munir; et al. (Environmental Science and Pollution Research, 2022)

Bioaccumulation and transfer of zinc in soil plant and animal system: a health risk assessment for the grazing animals - Fu Chen; Fatima Ghulam Muhammad; Zafar Iqbal Khan; Kafeel Ahmad; Ifra Saleem Malik; Asma Ashfaq; Majida Naeem; Muhammad Nadeem; Jing Ma; Muhammad Umer Farooq Awan; Shahzadi Mahpara; Shahid Mehmood (Environmental Science and Pollution Research, 2022)

Whole exome sequencing revealed novel variants in consanguineous Pakistani families with intellectual disability - Iqra Ghulam Rasool; Muhammad Yasir Zahoor; Muhammad Iqbal; Aftab Ahmad Anjum; Fatima Ashraf; Hafiz Qamar Abbas; Hafiz Muhammad Azhar Baig; Tariq Mahmood; Wasim Shehzad (Genes & Genomics, 2021)

Quantification of Climate Warming and Crop Management Impacts on Phenology of Pulses-Based Cropping Systems - Zartash Fatima; Atique-ur-Rehman; Ghulam Abbas; Pakeeza Iqbal; Iqra Zakir; Muhammad Azam Khan; Ghulam Mujtaba Kamal; Mukhtar Ahmed; Shakeel Ahmad (International Journal of Plant Production, 2021)

Sowing Date and Hybrid Choice Matters Production of Maize–Maize System - Ghulam Abbas; Shakeel Ahmad; Mubshar Hussain; Zartash Fatima; Sajjad Hussain; Pakeeza Iqbal; Mukhtar Ahmed; Muhammad Farooq (International Journal of Plant Production, 2020)

Changes in extreme temperature and precipitation in the Arab region: long‐term trends and variability related to ENSO and NAO - M. G. Donat; T. C. Peterson; M. Brunet; A. D. King; M. Almazroui; R. K. Kolli; Djamel Boucherf; Anwar Yousuf Al‐Mulla; Abdourahman Youssouf Nour; Ahmed Attia Aly; Tamer Ali Ali Nada; Muhammad M. Semawi; et al. (International Journal of Climatology, 2014)
A workshop was held in Casablanca, Morocco, in March 2012, to enhance knowledge of climate extremes and their changes in the Arab region. This workshop initiated intensive data compilation activities of daily observational weather station data from the Arab region. After conducting careful control processes to ensure the quality and homogeneity of the data, climate indices for extreme temperatures and precipitation were calculated. This study examines the temporal changes in climate extremes in the Arab region with regard to long‐term trends and natural variability related to ENSO and NAO . We find consistent warming trends since the middle of the 20th Century across the region. This is evident in the increased frequencies of warm days and warm nights, higher extreme temperature values, fewer cold days and cold nights and shorter cold spell durations. The warming trends seem to be particularly strong since the early 1970s. Changes in precipitation are generally less consistent and characterised by a higher spatial and temporal variability; the trends are generally less significant. However, in the western part of the Arab region, there is a tendency towards wetter conditions. In contrast, in the eastern part, there are more drying trends, although, these are of low significance. We also find some relationships between climate extremes in the Arab region and certain prominent modes of variability, in particular El Niño‐Southern Oscillation ( ENSO ) and North Atlantic Oscillation ( NAO ). The relationships of the climate extremes with NAO are stronger, in general, than those with ENSO , and are particularly strong in the western part of the Arab region (closer to the Atlantic Ocean). The relationships with ENSO are found to be more significant towards the eastern part of the area of study. © 2013 Royal Meteorological Society